Low-Income Black Parents Supporting Their Children’s Success through Mentoring Circles - Butler, Alana (Canadian Journal of Education / Revue canadienne de l'éducation, 2021)
This article presents the results of a parent engagement project called “Mentoring Circles.” The project focused on the needs of low-income Black parents who have children enrolled in the Toronto District School Board. Two focus groups, with seven to eight Black parents in each group, were conducted during the summer of 2018. The study drew on theories of community wealth and funds of knowledge (González et al., 2005; Yosso, 2005), Black feminist theory (Collins, 2000; Crenshaw, 1991), and critical race theory (Delgado & Stefancic, 2012). The Black parent narratives served as counter-stories to stereotypes about Black parent disengagement in low-income communities. The low-income Black parents in the study were very engaged in their children’s education and were invested in their academic success. The Black parents strategized to support their children’s education by forming supportive peer mentoring networks and advocating for their children though relationship-building. The findings suggest that mentoring circles could serve as a model for engaging Black parents in the support of their children’s academic success.